Correlation of Specific Platelet Activation Markers with Carotid Arterial Wall Thickness - Ghaddar, Habib M; Cortes, Jorge; Salomaa, Veikko; Kark, Jeremy D; Davis, C Edward; Folsom, Aaron R; Heiss, Gerardo; Stinson, Valarie; Wu, Kenneth K; For the Atherosclerosis Risk in Communities Study Investigators (Thrombosis and Haemostasis, 1995)
Many studies have shown inereased platelet activation in patients with coronary artery, cerebrovascular and peripheral vascular diseases. However, the temporal relationship between platelet activation and arterial atherosclerosis is unclear. To answer this basic question, we measured the plasma concentrations of two specific platelet activation markers, β-thromboglobulin (βTG) and platelet factor 4 (PF4) in 459 cases with increased carotid arterial wall thickness and 459 age-, sex- and race-matched controls selected from a cohort of 15,800 men and women, aged 45-64 who participated in the Atherosclerosis Risk in Communities Study. These participants had no acute vascular symptoms or known cardiovascular disease. The mean values of βTG and PF4 were significantly higher in cases than in controls. However, when analyzed by quartiles using conditional logistic regression, only βTG exhibited a significant association with carotid wall thickness, while PF4 did not. The odds ratio (OR) determined by multivariate logistic regression analysis was significantly higher for the uppermost quartile of βTG (OR=1.7, 95% Cl 1.1-2.5) compared to the lower 3 quartiles. This OR was 2.3 in white men (95% Cl 1.2-4.2), 1.4 in white women (95% Cl 0.6-3.0) and 1.0 in blacks (95% Cl 0.4-2.5).This study indicates that plasma βTG may be useful as a marker for early atherosclerosis in middle aged adults, particularly in white men. It also suggests that platelet activation has an independent role in the pathogenesis of atherosclerosis, although the possibility that this may be a response to carotid atherosclerosis cannot be excluded.